Antigen Loss Variants: Catching Hold of Escaping Foes - Vyas, Maulik; Müller, Rolf; Pogge von Strandmann, Elke (Frontiers in Immunology, 2017)
Since mid-1990s, the field of cancer immunotherapy has seen steady growth and selected immunotherapies are now a routine and preferred therapeutic option of certain malignancies. Both, active and passive cancer immunotherapies exploit the fact that tumor cells express specific antigens on the cell surface, thereby mounting an immune response specifically against malignant cells. It is well established that cancer cells typically lose surface antigens following natural or therapy-induced selective pressure and these antigen-loss variants are often the population that causes therapy-resistant relapse. CD19 and CD20-antigen-loss in acute lymphocytic leukemia (ALL) and chronic lymphocytic leukemia (CLL), respectively and lineage switching in leukemia associated with mixed lineage leukemia (MLL) gene rearrangements are well documented evidences in this regard. Although, increasing number of novel immunotherapies are being developed, majority of these do not address the control of antigen loss variants. Here, we review the occurrence of antigen loss variants in leukemia and discuss the therapeutic strategies to tackle the same. We also present an approach of dual-targeting immunoligand effectively retargeting NK cells against antigen loss variants in MLL associated leukemia. Novel immunotherapies simultaneously targeting more than one tumor antigen certainly hold promise to completely eradicate tumor and prevent therapy-resistant relapses.